1999
DOI: 10.1097/00005373-199908000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Tone in Patients with Hemorrhagic Shock

Abstract: These data demonstrate that the Ev increases in hemorrhagic shock. Furthermore, normotensive hypovolemic conditions generated by persistent bleeding can be detected by measuring the Ev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Dutch and Redman (1983) studied cardiovascular activity during psychological stressors with significant PTT decreases measured during the cold-pressor test, reaction-time task, video game and problem solving. Vascular tone, that is the degree of vasoconstriction experienced by a blood vessel relative to its maximally dilated state, has also been assessed in patients with haemorrhagic shock (Miyagatani et al 1999), following mood changes whilst listening to music (Matsuura 2002), genital haemodynamics in sexual dysfunction (Prause et al 2005, Brauer et al 2006, physiological studies (Foo andLim 2006a, Foo et al 2006), haemodialysis (Burkert et al 2006), and the ambulatory monitoring of patients prone to hypoglycaemic events (Harris et al 1996).…”
Section: Neurologymentioning
confidence: 99%
“…Dutch and Redman (1983) studied cardiovascular activity during psychological stressors with significant PTT decreases measured during the cold-pressor test, reaction-time task, video game and problem solving. Vascular tone, that is the degree of vasoconstriction experienced by a blood vessel relative to its maximally dilated state, has also been assessed in patients with haemorrhagic shock (Miyagatani et al 1999), following mood changes whilst listening to music (Matsuura 2002), genital haemodynamics in sexual dysfunction (Prause et al 2005, Brauer et al 2006, physiological studies (Foo andLim 2006a, Foo et al 2006), haemodialysis (Burkert et al 2006), and the ambulatory monitoring of patients prone to hypoglycaemic events (Harris et al 1996).…”
Section: Neurologymentioning
confidence: 99%
“…Catecho-lamines and adrenocorticotrophic hormones assume a marked role in response to haem-orrhage [9,4]. Immediate post-haemorrhagic hyperthermia has been reported in previous studies in goats [14,20,21].…”
Section: Thermoregulation and Heart Rate (Hr)mentioning
confidence: 90%
“…The primary physiologic response to compensate for haemorrhagic shock is via the sympathetic nervous system; baroreceptors in the carotid sinus and chemoreceptors sense hypovolaemia and hypoxaemia, respectively [8]. Also, endocrine-mediated mechanisms help to maintain perfusion in shock; the release of catecholamines activates α 1 receptors in the peripheral vascular smooth muscle causing peripheral vasoconstriction [9]. Proportional increase in heart rate (HR) and a decrease in mean arterial pressure (MAP) have been reported in animals exposed to haemorrhage [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that an intense redistribution of blood flow from non-vital organs to vital organs characteristically occurs in states of shock, causing peripheral hypoperfusion. ( 31 ) The peripheral hypoperfusion is generated by an increase in sympathetic-neurohumoral activity ( 31 , 32 ) and is associated with worse systemic perfusion and poor prognosis. ( 15 , 32 ) Since previous reports showed that the PI is a very sensitive method for assessing adrenergic responses, ( 33 , 34 ) the adrenergic stimulus (secondary to the sympathetic response to shock and to use of vasopressors) also becomes a direct hypothesis that could explain the relatively preserved peripheral vascular reactivity despite the peripheral hypoperfusion in the septic group: it implies the existence of a peripheral ischemic reserve in septic shock.…”
Section: Discussionmentioning
confidence: 99%